[Church and Homes at Thingvellir] - Streng, Evelyn Fiedler (1975)
Photograph of a church and homes at Thingvellir. A row of connected, white houses with grey roofs and green doors sits to the right past green trees. A small, white church covered in grey roofs sits at the center of the photograph. A rectangular church tower sits along the face of the church. A flagpole holding up the Icelandic flag. A bumpy, grassy field stretches across the photograph, a dark river sitting in the foreground. A person in orange is knelt down in the dirt across the river.